Ideological Dissonance in a Literature Teaching Process - Moral Conflicts in a Democratic and Nationally Diverse Society: A Case Study of Israeli Teachers - Lea Baratz; Roni Reingold (Arizona State University, 2010)
The current study examines the implications of literary teaching material in a national diversified society in which the governmental educational policy separates between two national educational systems, and controls both of these separate systems. We set out to examine whether, in such realty, teachers are willing to teach texts, not formally included in the curriculum, that are replete with values and politics. In addition, we examine if they are willing to teach, whether they would introduce their ideological beliefs even if the teaching unit is incompatible with their ideological worldview. The teaching material comprises two poems about Jerusalem, one written by a Jewish poet and the other by an Israeli Palestinian poet. 26 Interviews were preformed with teachers: 13 Jews and 13 Palestinians. Their sayings were categorized into the following voices: The essence of the voice â a captured or liberated voice; Character of the voice â neutral or political; and Aim of the voice â socialization or individualization. We did not find any differences in the voices among the Palestinian and the Jewish teachers. Categorically, the teachers attempted to silence any discussion that spilled over into political matters. The ideological dilemma made the teachers voice as hidden voice. Since, we do not believe that the governmental educational policy in Israel is going to become more democratic, we hope that our findings will encourage colleges of education in Israel and similar societies to encourage their students to develop liberated and political voices, and voices of individualization.